2004
DOI: 10.1089/thy.2004.14.926
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Disorders in the Working Population of Germany: Ultrasonography Screening in 96,278 Unselected Employees

Abstract: Germany continues to be iodine deficient despite considerable improvement in the past years. To assess the current prevalence of diffuse and/or nodular thyroid disorders, a cross-sectional observational study in a nonrandom sample of the working population was carried out throughout Germany in 2001 and 2002. A total of 96,278 employees 18-65 years of age from 214 companies or other private or public institutions voluntarily underwent ultrasonographic examinations by 230 experienced investigators. To compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
0
52

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(218 citation statements)
references
References 21 publications
(8 reference statements)
11
155
0
52
Order By: Relevance
“…Previous ultrasound studies from Germany on adults reported inconsistent results regarding the prevalence of thyroid ultrasound findings. While, for example, pathological changes of the thyroid (goiter/nodules and suspected autoimmune thyroiditis) in untreated persons were observed in 70% of the study conducted by Guth et al (34), the corresponding proportion was 33% in the Papillon study (35). A Finnish study conducted on middle-aged women found abnormalities of the thyroid gland as revealed by ultrasound examination in 35.6% (36).…”
Section: Discussionmentioning
confidence: 94%
“…Previous ultrasound studies from Germany on adults reported inconsistent results regarding the prevalence of thyroid ultrasound findings. While, for example, pathological changes of the thyroid (goiter/nodules and suspected autoimmune thyroiditis) in untreated persons were observed in 70% of the study conducted by Guth et al (34), the corresponding proportion was 33% in the Papillon study (35). A Finnish study conducted on middle-aged women found abnormalities of the thyroid gland as revealed by ultrasound examination in 35.6% (36).…”
Section: Discussionmentioning
confidence: 94%
“…The breakdown of students according to level of schooling was: 1.8% of preschool pupils (aged under 6), 36.7% of primary-school pupils (aged 6 to 11), 16.9% of secondary-school students (aged 12 to 17), and 44.6%…”
Section: Occupational Statusmentioning
confidence: 99%
“…Etiologies of laryngeal mobility disorders include malignancies, surgery, and idiopathic causes. Prevalence of thyroid disorders increases with age and thyroid cancer mostly occurs after fifty years of age [35,36]. Cantarella et al showed that the main etiology of unilateral vocal fold paralysis was thyroidectomy in middle aged patients, head and neck surgery in elderly patients, and idiopathic origin in the youngest patients [35].…”
Section: Diagnosismentioning
confidence: 99%
“…Goiter and/or thyroid nodules are the most prevalent endocrine conditions in the world, affecting over 500 million people with prevalence rates reaching up to 30 % [1,2]; local neck symptoms range from 13 to 50 % in patients undergoing surgery for benign nodular diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%